HOUSEFLIES (MUSCA DOMESTICA) AS POTENTIAL CARRIERS OF HUMAN INTESTINAL PARASITES IN JALINGO METROPOLIS - Elkanah, S. O.; Elkanah, D. S.; Fumlack, L. D.; Wahedi, Jasini; Kela, S. L. (FUDMA JOURNAL OF SCIENCES, 2020)
House flies (Musca domestica) are nuisance pest because of their ubiquitous nature in the mechanical transmission of parasites to man. This study identifies the pathogenic parasites associated with house fly in Jalingo, Nigeria. A total of 200 flies were collected from 4 locations (Abattoir, Jalingo Main Market, Kasuwan Bera and Mile-Six Market) within Jalingo metropolis between August, 2019 and November, 2019. Three species of flies were identified during the study namely; Musca spp, Sacophage spp and Stomoxys spp. The house flies were analyzed for the presence pathogenic parasites using standard laboratory techniques. The results showed that the parasites E. histolytica 25(28.74 %), Taenia spp 25(28.74 %), A. lumbricoides 20(22.99 %), Giardia lamblia 8(9.20 %) and Trichuris trichiura 9(10.34 %) are associated with the house flies. The results showed no significant variation (X2= 0.61, p>0.05) between the parasites species. It can be concluded that house flies in Jalingo harbor pathogenic parasites on their bodies. The fact that houseflies have been incriminated to be mechanical transmitters of pathogenic diseases to man because of their anthropogenic lifestyles, measures must be taken to control fly population in order to avert both the present and future outbreak of disease conditions emanating from the flies activities.
Keywords: Ascaris lumbricoides, Entamoeba histolytica. Giardia lamblia, Taenia spp, Trichuris trichiura.